PROFIL KEMAMPUAN KONEKSI MATEMATIS SISWA KELAS VIII SMPN 3 PALU DALAM MENYELESAIKAN MASALAH SOAL CERITA PADA MATERI KUBUS DI TINJAU DARI KEMAMPUAN MATEMATIKA - Lestari, Nur Ayu Enda; Bennu, Sudarman; Hasbi, Muh.; Sugita, Gandung (Universitas Tadulako, 2023)
The study was to describe the ability of the eighth graders' mathematical connections to solve problems based on mathematical abilities. This type of research is a qualitative study. The subject of this study is the eighth grade 1 st student hammer with a high level, moderate ability and low capacity. The method of data collection with observation, tests and interviews through the technical data analysis phase that is the condensing of data, the presentation of data and the drawing of conclusions. The stability of mathematical connections is defined by the mathematical problem of the cube that contains the indicator of the ability of mathematics: 1) connections between mathematical concepts, 2) connections between mathematics and other disciplines, 3) connections connecting and applying mathematics in everyday life. Research shows that high-performing students are able to meet the indicator of mathematical connection capability, the gifted student only meets a portion of the mathematical competence and the underprivileged student is not yet able to meet the indicator of mathematical connection.